2009
DOI: 10.1007/s00253-009-2320-1
|View full text |Cite
|
Sign up to set email alerts
|

Light regulation of metabolic pathways in fungi

Abstract: Light represents a major carrier of information in nature. The molecular machineries translating its electromagnetic energy (photons) into the chemical language of cells transmit vital signals for adjustment of virtually every living organism to its habitat. Fungi react to illumination in various ways, and we found that they initiate considerable adaptations in their metabolic pathways upon growth in light or after perception of a light pulse. Alterations in response to light have predominantly been observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
199
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(207 citation statements)
references
References 202 publications
(275 reference statements)
4
199
1
3
Order By: Relevance
“…Our low numbers of strains were probably due to selection favoring only some strains. Some species of fungi require light to induce sporulation and metabolic activity (Tisch and Schmoll, 2010), and these species will have more difficulty surviving in the cave environment. The input of microorganisms by dripping water and periodic flooding of the river may carry organisms that cannot survive the cave conditions and are used by opportunistic fungi as a source of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Our low numbers of strains were probably due to selection favoring only some strains. Some species of fungi require light to induce sporulation and metabolic activity (Tisch and Schmoll, 2010), and these species will have more difficulty surviving in the cave environment. The input of microorganisms by dripping water and periodic flooding of the river may carry organisms that cannot survive the cave conditions and are used by opportunistic fungi as a source of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Our results clearly show the interesting observations that fungi respond to light and initiate considerable adaptations in their metabolic pathways during growth. Alterations in response to light have been noted with respect to carotenoid metabolism, polysaccharide and carbohydrate metabolism, fatty acid metabolism, nucleotide and nucleoside metabolism, and in the regulation of secondary metabolite production (Tisch and Schmoll, 2010). Notably, considering the differences in favorable conditions for sexual and asexual development in various fungi, regulation of these changes may differ accordingly.…”
Section: Effect Of Light On the Growth Of A Oryzae (F6) A Oryzae F6mentioning
confidence: 99%
“…The RIB 1187 biomass grown on minimal media weighed 43.2 ± 0.4 mg when grown under the light condition, and weighed 40 ± 0.1 mg when grown under the dark condition, thereby showing 7.4% (P < 0.05) more growth under the light condition. Light has various effects on not only asexual development but also on the growth and metabolism of fungi (Tisch andSchmoll 2010, Atoui et al 2010). Our results also showed that light could affect not only asexual development but also the growth rate of RIB 1187.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, most fungi use light as a signal of the surface environment in adjusting to a new habitat (Rodriguez-Romero et al 2010). In adapting to the environment, fungi drastically change both gene expression and metabolic pathways (Rodriguez-Romero et al 2010, Tisch andSchmoll 2010). Fungi produce asexual structures toward the open air to facilitate spore dispersal in response to light (RodriguezRomero et al 2010, Ruger-Herreros et al 2011.…”
Section: Introductionmentioning
confidence: 99%